2001
DOI: 10.1093/alcalc/36.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Expression, but not activity, of neuronal nitric oxide synthase is regionally increased in the alcoholic brain

Abstract: The regional distribution of nitric oxide synthase (NOS) was investigated in alcoholic post-mortem brains compared with brains of non-alcoholic control individuals. Total enzyme activity in 28 brain regions was determined using the [(3)H]l-citrulline formation assay, whereas Western blot analyses were used for semi-quantitative measurement of the neuronal isoform of NOS (nNOS). In the alcoholic brain, nNOS protein expression was increased in the following regions: frontal cortex (85%), the cingulate gyrus (294… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…This may explain why no differences in total NO production could be observed despite a decrease in nNOS protein expression. Although it is not clear why such a counterregulatory mechanism occurs, a similar phenomenon has been reported in the alcoholic brain although in the opposite manner, with an increased expression of nNOS without a change in activity levels [38]. Conversely, it has been shown that NOS activity increases with ageing in the cortex and hippocampus of rats without a concomitant increase in nNOS protein expression [39–41].…”
Section: Discussionmentioning
confidence: 79%
“…This may explain why no differences in total NO production could be observed despite a decrease in nNOS protein expression. Although it is not clear why such a counterregulatory mechanism occurs, a similar phenomenon has been reported in the alcoholic brain although in the opposite manner, with an increased expression of nNOS without a change in activity levels [38]. Conversely, it has been shown that NOS activity increases with ageing in the cortex and hippocampus of rats without a concomitant increase in nNOS protein expression [39–41].…”
Section: Discussionmentioning
confidence: 79%
“…In addition, different NOS inhibitors are shown to attenuate place conditioning induced by nicotine, morphine, methamphetamine, alcohol, and cocaine Manzanedo et al 2004;Kivastik et al 1996;Langroudi et al 2005;Li et al 2002;Itzhak and Martin 2000;Kim and Park 1995;Itzhak et al 1998). It was reported that in the alcoholic brain, neuronal NOS protein content is increased in the frontal cortex and the nucleus accumbens brain regions, which were suggested to be involved in the dopaminergic mesolimbic reward system (Gerlach et al 2001). It was shown that NOS, guanylyl cyclase, and PDE-5 are present in high concentrations in regions of the brain involved in reward circuits (Garthwaite and Boulton 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Produced free radicals have a destructive effect on the tissues (Kono et al, 2000), especially by producing peroxinitrite radical in the reaction with NO (d' Ischia et al, 2000;Gerlach et al, 2001). Experiments dealing with the influence of alcohol beverages on the levels of some of the oxidative impairment markers bring controversial results.…”
Section: Discussionmentioning
confidence: 99%